Screening of Non-Communicable Diseases and their Risk Factors among Tuberculosis Patients in Delhi: A Mix Method Study - Kaur, Gurmeet; Kritika; Thakur, Vivek K (Indian Journal of Community Health, 2023)
Background: India has the highest burden of tuberculosis in the world. It is experiencing an increasing burden of noncommunicable diseases, thereby facing a dual disease burden. Recent evidence shows an association between TB and noncommunicable diseases like diabetes, CVD and chronic respiratory infections. Aims and Objectives: To assess the feasibility of screening for NCDs and risk factors for NCDs among patients with TB in DOTS centers of a medical college in Delhi and ascertain challenges for the same among providers and patients. Methodology: It was a mixed-methods study with a quantitative component (cross-sectional study using questionnaires, anthropometric measurements and records review) and a qualitative component (descriptive study using interview data). Results: Among the 139 patients screened, ten new cases of hypertension and six new patients were diagnosed with DM. Outof- pocket expenditure for tests was a concern of the patients. Health care providers found the screening tool easy to use but were apprehensive about increased workload Conclusion: The study provide useful visions for incorporating NCDs into routine TB care through DOTS centers under RNTCP/NTEP.